(3QSGdI aj PcQ CMGOjK de JUMs - (3GdMfaj GdNQGSGfj, CHh eMeO, GdnqUrOQ GdnqTpgjO, HQgGf GdCFeI, YeQ Hf YHO GdYRjR Hf YeQ Hf eGRI, (B536 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi QShdg eMeO hBdg hUMHg hSde eG GTJgQ ef Cf GdEjeGf bhd hYed hjRjO hjfbU hGdEjeGf dG jRjO hdG jfbU ef CbhGd GdUMGHI hGdJGHYjfs
(3BNQgG (B:s
(3hPe GdJYHO HdG abg hPe GdYdeGA hRjGQI GdedGFcI bHhQ GdYdeGA de jKHJ TjA haj GaJQGb GdCeI GKfjf (B( (3cPG (B) (3hSHYjf aQbI de jKHJ TjA hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 51s
(3eYLe GdeDdajf (B2 / 562s
(3GdLhGgQ GdeVjI (B1 / 391s
(3gOjI GdYGQajf (B1/ 783s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs